A zirconium-based metal organic framework material and its application in catalytic ring-opening copolymerization
By using the organic framework material of the 有 通过 to catalyze the opening and co -concentrations of epoxy oxides and the acidic anhydride, the problems of insufficient activity and side reactions in the existing technology have been solved, and efficient and sustainable polyester materials are achieved.
Patent Information
- Application Number
- CN202310354882.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-06
AI Technical Summary
The prior art has problems such as insufficient activity, many side reactions, and difficulty in recycling of catalysts in the ring-opening copolymerization of catalytic epoxides and cyclic anhydrides, which limits the sustainable production of polyester materials.
Zirconium-based metal-organic framework materials are used as catalysts, and the materials are prepared through hydrothermal reactions, and then undergo ring-opening copolymerization with epoxides and cyclic acid anhydrides under water-free, oxygen-free, and catalyst-free conditions.
It achieves efficient catalytic ring-opening copolymerization of epoxide and cyclic acid anhydride, reduces metal pollution, simplifies the process flow, and is suitable for mass production of polyester materials of different types and functions.
Smart Images

Figure CN116284830B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and particularly relates to a zirconium-based metal organic framework material and application thereof in catalyzing the ring-opening copolymerization of epoxides and cyclic anhydrides. Background Art
[0002] Aliphatic polyesters are expected to become a substitute for petroleum-based plastics due to their renewable monomers, easy recycling and biodegradability. However, the production process of industrial polyesters mainly adopts energy-intensive polycondensation reactions, and the production of small molecule byproducts limits the sustainable development of the process, so it is urgent to develop new green and sustainable synthesis methods. Ring-opening copolymerization (ROCOP) of epoxides and cyclic anhydrides can prepare polyester materials with controllable molecular weight and low dispersibility, providing a green and economical polymerization method for the synthesis of aliphatic polyesters. At present, ROCOP catalyst / cocatalyst systems usually show moderate to poor activity at low catalyst loadings and cannot avoid harmful side reactions such as epoxide homopolymerization, transesterification or isomerization.
[0003] Ring-opening copolymerization of epoxides and cyclic anhydrides catalyzed by homogeneous organometallic or Lewis acid catalysts is a good method for synthesizing high molecular weight polyesters. In these systems, the Lewis acid / nucleophilic cocatalyst system initiates polymerization, activates the ring opening of epoxides, and regulates the reactivity of the growing chain end. However, the residual metal catalyst makes it difficult to purify the polymer afterward, which limits further application. For this reason, it is necessary to use a recyclable solid catalyst so that the catalyst can be separated from the generated polymer product to achieve the purpose of reducing metal residues. However, there are few reports on heterogeneous catalytic systems for the ring-opening copolymerization of epoxides and cyclic anhydrides. Among them, most active solid catalysts are double metal cyanides, which have a high preparation cost and limit their application. Lewis acid centers can catalyze the ROCOP of epoxides and cyclic anhydrides to produce polyesters. Materials with Lewis acid centers and high specific surface areas are likely to become potential catalysts for this polymerization reaction.
[0004] Zirconium-based metal organic frameworks are formed by zirconium atoms and corresponding organic ligands, have a macroporous molecular sieve topology, have good thermal and chemical stability, and can be used as catalysts for studying ring-opening copolymerization. At the same time, zirconium-based metal organic framework materials are insoluble in most common organic solvents, show good stability in air, have significant chemical resistance to water and organic solvents, and have the potential for industrial application. Summary of the invention
[0005] The purpose of the present invention is to provide a zirconium-based metal organic framework material and its application in catalyzing the ring-opening copolymerization of epoxide and cyclic anhydride. The application process is simple and green, no auxiliary catalyst is required, no small molecule by-products are produced, and mass production of polyesters of different types and functions can be achieved, and the catalyst is easy to separate.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A zirconium-based metal organic framework material is prepared by uniformly mixing zirconium chloride, a dibasic acid ligand, and a mixed solvent consisting of DMF and glacial acetic acid by ultrasonication, then subjecting the mixture to a hydrothermal reaction at 120°C for 24 hours, and centrifuging, washing and drying the reaction solution after cooling.
[0008] Furthermore, the molar ratio of zirconium chloride to dibasic acid ligand is 1:1.
[0009] Furthermore, the dibasic acid ligand is any one of terephthalic acid, 2-nitroterephthalic acid, 2-aminoterephthalic acid, 2-bromoterephthalic acid, 4,4'-biphenyldicarboxylic acid, and [1,1':4',1''-terphenyl]-4,4''-dicarboxylic acid.
[0010] Furthermore, the zirconium-based metal organic framework material is specifically one of UIO-66, UIO-66-NO2, UIO-66-NH2, UIO-66-Br, UIO-67, and UIO-68.
[0011] The zirconium-based metal organic framework material can be used to catalyze the ring-opening copolymerization of epoxide and cyclic anhydride. Specifically, the zirconium-based metal organic framework material is mixed with epoxide and cyclic anhydride under the condition of no water, no oxygen and no promoter to carry out the ring-opening copolymerization reaction.
[0012] Furthermore, the molar ratio of the zirconium-based metal organic framework material, epoxide and cyclic anhydride is 1:(100-500):(10-200).
[0013] Furthermore, the epoxide is any one of cyclohexene oxide (CHO), epichlorohydrin (ECH), styrene oxide (SO), and phenyl glycidyl ether (PGE).
[0014] Furthermore, the cyclic anhydride is any one of maleic anhydride (MA), succinic anhydride (SA), phthalic anhydride (PA), and nadic anhydride (NA).
[0015] Furthermore, the ring-opening copolymerization reaction time is 5 min-12 h, and the temperature is 80°C-110°C.
[0016] The beneficial effects of the present invention are:
[0017] (1) Compared with homogeneous catalysts, heterogeneous catalysts are easier to separate from products and can reduce metal contamination in the products.
[0018] (2) Compared with the traditional production of polyester by polycondensation or ester exchange reaction, the present invention synthesizes polyester by ring-opening copolymerization of epoxide and cyclic anhydride, which does not require high temperature to remove small molecular by-products and is more in line with green chemistry and atom economy.
[0019] (3) Compared with lactone monomers, the preparation of epoxides and cyclic anhydrides is simpler and more economical. Currently, most epoxide and cyclic anhydride raw materials can be produced in large quantities. Therefore, the ring-opening copolymerization of epoxides and cyclic anhydrides is more suitable for the preparation of polyesters of different types and functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD comparison diagram of different zirconium-based MOFs shows that the synthesized MOFs have good crystallinity.
[0021] Figure 2 The figure shows the comparison of the catalytic effects of different zirconium-based MOFs on CHO and MA (110 ℃, 0.5 h). It can be seen from the figure that UIO-67 has the best catalytic effect.
[0022] Figure 3 The catalytic kinetics comparison diagram of UIO-66 at different temperatures shows that the reaction is a first-order kinetic reaction.
[0023] Figure 4 The SEM comparison pictures of UIO-66 before (left) and after (right) use in Example 2 are shown. As can be seen from the picture, there is no significant change in the morphology of UIO-66 before and after the reaction.
[0024] Figure 5 This is the XRD comparison diagram (110 °C, 4 h) of UIO-66 after five cycles in Example 3. It can be seen from the figure that the crystallinity does not change much after five cycles.
[0025] Figure 6 This is a diagram showing the catalytic effect of UIO-66 after five times of use in Example 3 (110°C, 4 h). It can be seen from the figure that it still has good catalytic activity after five times of use.
[0026] Figure 7 The polyester obtained in Example 11 1 H NMR spectrum.
[0027] Figure 8 The GPC spectrum of the polyester obtained in Example 11 is shown in the figure. Mn =4600, PDI=1.52. DETAILED DESCRIPTION
[0028] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0029] Example 1
[0030] 0.227 mmol zirconium chloride and 0.227 mmol terephthalic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to mix them evenly. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol, respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-66.
[0031] Example 2
[0032] In anhydrous and oxygen-free environment, UIO-66 obtained in Example 1 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 2 h. The product was sampled for nuclear magnetic resonance analysis, dissolved with dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =4100, PDI=1.48.
[0033] Example 3
[0034] In an anhydrous and oxygen-free environment, UIO-66 obtained in Example 1 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for 4 hours. The product was sampled for nuclear magnetic resonance analysis, dissolved with dichloromethane, and the precipitate was washed three times with dichloromethane and methanol after centrifugation. After drying in a 60°C vacuum drying oven, the same conditions were cycled for 5 times for testing; the supernatant was precipitated with anhydrous methanol to obtain a polymer, which was sampled for molecular weight testing after centrifugal vacuum drying. The results showed that M n =3700, PDI=1.51.
[0035] Example 4
[0036] In anhydrous and oxygen-free environment, UIO-66 obtained in Example 1 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 100°C constant temperature reaction bath for reaction for 160 min. The product was sampled for nuclear magnetic resonance analysis, dissolved with dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =3800, PDI=1.68.
[0037] Example 5
[0038] In anhydrous and oxygen-free environment, UIO-66 obtained in Example 1 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 90°C constant temperature reaction bath for 4 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =3100, PDI=1.61.
[0039] Example 6
[0040] In anhydrous and oxygen-free environment, UIO-66 obtained in Example 1 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 80°C constant temperature reaction bath for 6 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =3800, PDI=1.51.
[0041] Example 7
[0042] 0.227 mmol zirconium chloride and 0.227 mmol 2-nitroterephthalic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to mix them evenly. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol, respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-66-NO2.
[0043] In an anhydrous and oxygen-free environment, the obtained UIO-66-NO2 was added to the Schlenk tube in a molar ratio of 1:100:30 with CHO and MA. After being stirred evenly at room temperature, it was placed in a set 110 ℃ constant temperature reaction bath for reaction for 0.5 h. After the product was sampled for NMR analysis, it was dissolved in dichloromethane and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =3200, PDI=1.66.
[0044] Example 8
[0045] 0.227 mmol zirconium chloride and 0.227 mmol 2-aminoterephthalic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to make it evenly mixed. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-66-NH2.
[0046] In an anhydrous and oxygen-free environment, the obtained UIO-66-NH2, CHO, and MA were added to the Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110 ℃ constant temperature reaction bath for reaction for 0.5 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, samples were taken for molecular weight testing. The results showed that M n =3200, PDI=1.56.
[0047] Example 9
[0048] 0.227 mmol zirconium chloride and 0.227 mmol 2-bromoterephthalic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to make it evenly mixed. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol, respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-66-Br.
[0049] In anhydrous and oxygen-free environment, the obtained UIO-66-Br, CHO, and MA were added to the Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110 ℃ constant temperature reaction bath for 0.5 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, samples were taken for molecular weight testing. The results showed that M n =4100, PDI=1.66.
[0050] Example 10
[0051] 0.227 mmol zirconium chloride and 0.227 mmol 4,4'-biphenyldicarboxylic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to make it evenly mixed. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol, respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-67.
[0052] Embodiment 11
[0053] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and CHO and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 0.5 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =4600, PDI=1.52.
[0054] Example 12
[0055] 0.227 mmol zirconium chloride and 0.227 mmol [1,1':4',1''-terphenyl]-4,4''-dicarboxylic acid were added to a hydrothermal autoclave, and then 38 mL DMF and 2.1 mL glacial acetic acid were added, and ultrasonicated for half an hour at room temperature to mix them evenly. The hydrothermal autoclave was then placed in a 120 °C oven to react for 24 h. After cooling, the reaction solution was centrifuged at 8000 rpm for 3 min. The product was washed three times with DMF and anhydrous methanol, respectively, and finally dried in vacuum at 60 °C to obtain a powdered solid UIO-68.
[0056] In an anhydrous and oxygen-free environment, the obtained UIO-68, CHO, and MA were added to the Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110 ℃ constant temperature reaction bath for reaction for 0.5 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, samples were taken for molecular weight testing. The results showed that M n =1500, PDI=2.76.
[0057] Example 13
[0058] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and CHO and SA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 0.5 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =2800, PDI=2.01.
[0059] Embodiment 14
[0060] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and CHO and PA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 50 min. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, the sample was taken for molecular weight test. The results showed that M n =2000, PDI=1.69.
[0061] Embodiment 15
[0062] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and CHO and NA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 2 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =3100, PDI=2.11.
[0063] Example 16
[0064] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and ECH and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 10 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, the sample was taken for molecular weight test. The results showed that M n =1500, PDI=1.88.
[0065] Embodiment 17
[0066] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and SO and MA in a molar ratio of 1:100:30 were added to a Schlenk tube in sequence, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 10 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, a sample was taken for molecular weight test. The results showed that M n =1200, PDI=1.90.
[0067] Embodiment 18
[0068] In anhydrous and oxygen-free environment, UIO-67 obtained in Example 10 and PGE and MA were added to a Schlenk tube in a molar ratio of 1:100:30, stirred evenly at room temperature, and placed in a set 110°C constant temperature reaction bath for reaction for 10 h. The product was sampled for nuclear magnetic resonance analysis, dissolved in dichloromethane, and precipitated with anhydrous methanol to obtain a polymer. After centrifugal vacuum drying, the sample was taken for molecular weight test. The results showed that M n =3300, PDI=1.12.
[0069] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. Application of a zirconium-based metal organic framework material in catalyzing the ring-opening copolymerization of epoxides and cyclic anhydrides, characterized in that: In the absence of water, oxygen and catalyst, the zirconium-based metal organic framework material is mixed with epoxide and cyclic anhydride to carry out a ring-opening copolymerization reaction; The zirconium-based metal organic framework material is prepared by adding 0.227 mmol of zirconium chloride and 0.227 mmol of 4,4'-biphenyl dicarboxylic acid into a hydrothermal kettle, and then adding 38 mL of DMF and 2.1 mL of glacial acetic acid, and then ultrasonicating at room temperature for half an hour to make the mixture evenly mixed, and then placing the hydrothermal kettle into a 120°C oven to react for 24 hours, and after cooling, centrifuging the reaction solution at 8000 rpm for 3 minutes, and washing the product with DMF and anhydrous methanol for 3 times, respectively, and finally vacuum drying at 60°C to obtain a powdered solid UIO-67.
2. The use according to claim 1, characterized in that: The molar ratio of the zirconium-based metal organic framework material, epoxide and cyclic anhydride is 1:(100-500):(10-200).
3. The use according to claim 1 or 2, characterized in that: The epoxide is any one of cyclohexene oxide, epichlorohydrin, styrene oxide and phenyl glycidyl ether.
4. The use according to claim 1 or 2, characterized in that: The cyclic anhydride is any one of maleic anhydride, succinic anhydride, phthalic anhydride and nadic anhydride.
5. The use according to claim 1, characterized in that: The ring-opening copolymerization reaction time is 5 min-12 h, and the temperature is 80°C-110°C.
Citation Information
Patent Citations
Normal-pressure preparation method of zirconium metal-organic framework material UIO-66
CN111333851A
Method for catalyzing ring-opening copolymerization of epoxide and cyclic anhydride by metal organic framework
CN113912829A